Implementation of employee green behavior in improving green practice at the grand hyatt hotel Bali - Yuliana, Mayang Ratu Anjelita; Sutarma, I Gusti Ngurah; Susanto, Budi (Journal of Commerce, Management, and Tourism Studies, 2024)
This research aims to analyze the implementation of employee green behavior in improving green practices at the Grand Hyatt Bali Hotel. The data collection methods used were interviews, questionnaires, and documentation. The respondents in this study were 86 employees who worked at the Grand Hyatt Bali Hotel. The analysis techniques used in this research are quantitative descriptive analysis and quantitative data analysis using simple linear regression analysis. Before the analysis is carried out, a reliability test and validity test are carried out on the questionnaire that will be distributed to respondents. The results of the quantitative analysis research show that the reliability test results on the employee green behavior variable have a Cronbanch's Alpha value of 0.819 and the green practice variable is 0.896, which shows that each variable has a value greater than Cronbanch's Alpha in the range of 0.60 in the correlation test. The test results between the employee green behavior and green practice variables at the Grand Hyatt Bali Hotel obtained a Pearson Correlation value of 0.559. With a significance value of <0.05, it can be concluded that the variables are correlated and have a positive correlation relationship. This shows that if there is an increase in the employee green behavior variable, it will be followed by an increase in the green practice variable. It can be concluded that employee green behavior has an influence on green practices, but several indicators need to be improved again so that the implementation of employee green behavior can run efficiently in improving green practices.